PENINGKATAN PENGETAHUAN TENTANG KESPRO DALAM RANGKA MENURUNKAN KEJADIAN KEHAMILAN PADA REMAJA - Silfia Angela Norce Halu; Yosef Firman Narut (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Adolescents who get information about reproductive health are only about 59% in young women and 55% in young men. As many as 12% of pregnancies occur in adolescent girls and 7% of adolescent boys are forced to have a partner resulting from an unexpected pregnancy. At SMPN6 Ruteng-Rentung, every year there are two or more students who drop out of school by reason of pregnancy outside marriage and that marriage and the students have not received counseling about reproductive health. Targets and outcomes which are the main objectives of increasing adolescent knowledge about reproductive health so as to reduce the number of pregnancy events outside of marriage. The method of implementation includes a pretest with a questionnaire continuing counseling about adolescent reproductive health and ending with a post-test using the same questions at the pre-test. The results obtained from 95 adolescents, before giving counseling there were 11 adolescents (11.5%) with good knowledge and 84 adolescents (88.5%) with less knowledge. After being given counseling about reproductive health, as many as 73 adolescents (76.8%) had good knowledge and 22 adolescents (23.2%) with less knowledge. Counseling about reproductive health activities are proven to increase knowledge of adolescents about reproductive health.